(untitled) (Revista Española de Fisiología, 1969)
Sialic acids. X. Content in acylneuraminic acids of several dietetical products (maternized milks) The nature and concentration of the sialic acids existing in eight dietetical products (matemized milks) generally employed as baby food in Western Europe are studied. The following neuraminderivatives were identified and determinated: N-glycoIylneuraminic acid (NGNA) (at the rat of 5-12 % against the whole acyl neuraminic acids, in two produets), N-ace-tylneuraminic acid (NANA) as the most important), one pluriacetylneuraminic acid and neuraminlactose (both in a variable percentage). The yield of sialic acids, expressed as NANA, varies deeply from one product to another, between 22 and 62 mg/100g of product. If their mean concentration (referred to mg/100 mi of «reconstituted milk») is compared with that of the cow, it may be observed that it is relatively poor. The difference is bigger yet if their concentration is compared with that of human milk. The influence of several factors in those valúes are commented and the eventual importance of sialic acids in the infant food is discussed.